(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Microtomography is successfully used in the odontological evaluation and treatments, as it´s capable to analyze the bone tissue and any possible damage in its root canal caused by a surgical intervention. In this study, the microCT was used to analyze the images by using different parameters in the acquisition process, as two matrix sizes: 1120x1120 pixels and 2240x2240 pixels. After the reconstruction, the volume of the root canal was analyzed, as well as the quantification of a remaining tooth closure material. The results showed that the detector array 1120X1120 was able to capture values close to those of the 2240x2240 matrix for the volume of root canal and for the residual material after treatment. Remaining tooth closure material correspond an average of 0.95 mm³ for 1120x1120 pixels, while the corresponding volume for 2240x2240 pixels was 0.90 mm³. Results for root canal volume average was 10.32 mm³ for 1120x1120 pixels, while for 2240x2240 pixels was 10.22 mm³. In this way, the difference of the detected volume between the two matrices is of 5.47% for the residual material and 0.93% for root canal volume. In a qualitative analyze, the 2240x2240 matrix allows the identification of a greater amount of details. However, it was possible to verify that depending on the application and the region of interest studied the smaller matrix can offer reliable results and a shorter processing time.